Kedaulatan Pangan Matrilineal: Aliran Remitansi dan Kekuasaan Pengambilan Keputusan Ibu dalam Rumah Tangga - Ofanto Ofanto; Elfindri Elfindri; Delfia Tanjung Sari (Jurnal Ecogen, 2025)
This study investigates the dynamics of household food sovereignty within matrilineal communities in West Sumatra, Indonesia, by analyzing the role of remittances managed by female household heads. Anchored in the theoretical framework of food sovereignty and embedded livelihood systems, this research applies a descriptive-quantitative method using Susenas microdata, with a focus on household structure, remittance sources, and food access indicators. The findings reveal that elderly women, especially widows, serve as primary decision-makers in allocating remittances to meet household food needs. While matrilineal norms grant symbolic authority to women, persistent food insecurity in remittance receiving households particularly in rural areas indicates a disconnect between financial inflows and food system resilience. This study reframes remittance not merely as monetary support, but as a strategic vehicle for advancing household-level food sovereignty. The findings align with Sustainable Development Goal 2 (Zero Hunger) and SDG 12 (Responsible Consumption and Production), and underscore the need for context-sensitive food policies that recognize gendered household roles in resource governance.